2022
DOI: 10.3390/universe8070346
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Geomagnetic Storm Main Phase and the Corresponding Solar Wind Parameters on 21–22 October 1999

Abstract: We use the SYM-H index to indicate the ring current index. We find that there were two periods during which the SYM-H index decreased quickly during the main phase of the geomagnetic storm on 21–22 October 1999. The first period from 11:44 p.m. UT on 21 October 1999 to 1:35 a.m. UT on 22 October 1999 is defined as step 1. Another period from 3:36 a.m. UT to 5:49 a.m. UT on 22 October 1999 is defined as step 3. The durations of step 1 and step 3 are defined as Δt1 and Δt3, respectively. The variation of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, (Wang et al 2003a) showed that the SGS on 2001 March 31 was due to the multiple magnetic clouds, which were formed by the overtaking of successive magnetic clouds. Case studies (Cheng et al 2020;Li et al 2022;Liu et al 2022) found that the solar wind density or dynamic pressure played an important role in the ring current increase speed in the SGS on 2001 March 31 and the great geomagnetic storm on 1999 October 21-22. Statistical studies (Le et al 2020;Zhao et al 2021;Gopalswamy et al 2022;Zhao et al 2022) proved that solar wind dynamic pressure is an important factor for the geomagnetic storm intensity besides the solar wind speed and the southward component (hereafter B s ) of interplanetary magnetic field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, (Wang et al 2003a) showed that the SGS on 2001 March 31 was due to the multiple magnetic clouds, which were formed by the overtaking of successive magnetic clouds. Case studies (Cheng et al 2020;Li et al 2022;Liu et al 2022) found that the solar wind density or dynamic pressure played an important role in the ring current increase speed in the SGS on 2001 March 31 and the great geomagnetic storm on 1999 October 21-22. Statistical studies (Le et al 2020;Zhao et al 2021;Gopalswamy et al 2022;Zhao et al 2022) proved that solar wind dynamic pressure is an important factor for the geomagnetic storm intensity besides the solar wind speed and the southward component (hereafter B s ) of interplanetary magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, only the SYM-H index can describe the rapid variation of the ring current although there is some difference between Dst index and SYM-H index (Katus & Liemohn 2013). It has been proved that the temporal variation of the solar wind parameters correlates well with that of the SYM-H index, but not with that of Dst index (Li et al 2022). The variation of the SYM-H index during the main phase of a geomagnetic storm (hereafter ΔSYM-H) is usually different from the minimum of SYM-H (SYM-H min ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the IMF is southward, the magnetic reconnection makes the solar wind energy enter the magnetotail region, and when the energy accumulates to a certain extent, the explosive release of particles and energy into the near-Earth space will eventually produce global geomagnetic disturbances. For different physical processes, the time between changes in interplanetary parameters and the response of the magnetosphere will vary, ranging from minutes to days (e.g., [39][40][41][42]). For example, ULF waves in the magnetosphere can be observed at ground-based geomagnetic stations rather quickly after a sudden increase in solar wind dynamic pressure [39], it takes about 30∼60 min for the solar wind energy to be injected into the magnetosphere and accumulated in the magnetotail [43], the formation of global geomagnetic storms will take longer delay time [44].…”
Section: Statistical Analysis Of Magnetic Storm Eventsmentioning
confidence: 99%
“…Rakhmanova et al [10] investigated the transformation of a turbulent cascade behind a quasi-perpendicular bow shock in the magnetosheath depending on the type of large-scale phenomena of solar wind interacting with the Earth's magnetosphere. Li et al [11] analyzed the dynamics of the solar wind that caused a complex, multistep, magnetic storm on 21-22 October 1999.…”
mentioning
confidence: 99%